Identification and characterization of EYD1, encoding an erythritol dehydrogenase in Yarrowia lipolytica and its application to bioconvert erythritol into erythrulose. (January 2018) - Carly, Frédéric; Steels, Sébastien; Telek, Samuel; Vandermies, Marie; Nicaud, Jean-Marc; Fickers, Patrick
Highlights: Y. lipolytica is able to bio-convert erythritol into erythrulose. Gene YALI0F01650g, renamed as EYD1, encodes an erythritol dehydrogenase. Overexpression of EYD1 in a Y. lipolytica Δ eyk1 mutant permits the bioconversion of erythritol into erythrulose. Abstract: In this study, gene YALI0F01650g has been isolated and characterized. Several experimental evidences suggest that the identified gene, renamed EYD1, encodes an erythritol dehydrogenase. An efficient bioreactor process for the bioconversion of erythritol into erythrulose was also developed. Using constitutive expression of EYD1 in a Y. lipolytica mutant containing a disrupted EYK1 gene, which encodes erythrulose kinase, erythrulose could be synthesized from erythritol at a rate of 0.116 g/gDCW .h and with a bioconversion yield of 0.64 g/g.